2010
DOI: 10.1108/20425945201000018
|View full text |Cite
|
Sign up to set email alerts
|

Does poverty cause environmental degradation? Evidence from waste management practices of the squatter and low‐cost flat housholds in Kuala Lumpur

Abstract: This study examines whether or not the waste management practices of the poor households living in squatters and low‐cost flats in Kuala Lumpur are conducive to the environment. With the aim of accomplishing the above, the study empirically assesses knowledge, attitude and behaviour of the urban poor concerning their household solid waste management. With primary data collected from the level of living condition and waste management practices of the urban poor, the study employed a multiplicity of statistical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 2 publications
2
13
0
Order By: Relevance
“…Moreover, poverty plays an indirect role by limiting technical and resources capacity at all levels, thereby limiting awareness and research advancement. Against such backdrops, Murad and Nik (2010) sheds light that the cause and effect relationship between poverty and the environment can potentially be shaped better by tweaking on key socioeconomic variables and environmental practices of a particular community or region as the major governing factors.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, poverty plays an indirect role by limiting technical and resources capacity at all levels, thereby limiting awareness and research advancement. Against such backdrops, Murad and Nik (2010) sheds light that the cause and effect relationship between poverty and the environment can potentially be shaped better by tweaking on key socioeconomic variables and environmental practices of a particular community or region as the major governing factors.…”
Section: Discussionmentioning
confidence: 99%
“…Scholars preliminarily use barter trade to analyse the industrial evolution process in poverty-stricken areas and propose that product demand promotes the transformation of the industrial layout (Ross, 1976;Murad & Nik Mustapha, 2010). However, endogenous power cannot completely solve the industrial upgrading in poor areas.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Scholars believe that the focus of achieving well-off goals in poor areas is sustainable developmentthat is, pursuing economic benefits while taking into account environmental protection (Gustafsson & Sai, 2009;Murad & Nik Mustapha, 2010;Gad & Yaron, 2007). EKC (Environmental Kuznets Curve) scholars suggest that developing countries should choose an economical route of environmental protection in their development (Takawira, 2019), while more environmental risks exist in lowincome areas (Kremer, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Furthermore, in the study of the impact of other economic variables on disasters we can refer to research conducted by ( Murad. and Musthapa, 2010 ), In a study conducted in Kuala Lumpur Malaysia, it was found that there was a relationship between poverty and disaster.…”
Section: Introductionmentioning
confidence: 99%